The in vitro effect of carvacrol, a food additive, on the pathogenicity of O157 and non-O157 Shiga-toxin producing Escherichia coli. (February 2018) - Stratakos, Alexandros Ch; Sima, Filip; Ward, Patrick; Linton, Mark; Kelly, Carmel; Pinkerton, Laurette; Stef, Lavinia; Pet, Ioan; Corcionivoschi, Nicolae
Abstract: Shiga toxin producing Escherichia coli (STEC) are important pathogens implicated in foodborne outbreaks and severe human infections. E. coli O157:H7 is the most common strain amongst STECs however non-O157 STECs have been connected with numerous outbreaks worldwide. The use of natural plant extracts to reduce the risk from foodborne pathogens is gaining increasing importance. Therefore, the aim of the study was to investigate the effect of carvacrol against O157, O26, O45, O103, O111, O121, O145 and O104 at different concentrations. Changes in membrane permeability, membrane integrity and intracellular ATP levels were determined to further elucidate the possible antimicrobial mechanism. The effect of carvacrol on the phenotypic expression of virulence in terms of adhesion to human intestinal cells was also studied. Carvacrol had potent antibacterial effect against all strains. Treatment with carvacrol at different concentrations significantly affected the cell membrane permeability and reduced intracellular ATP levels for all STECs. It was also shown that exposure of STECs to carvacrol at sub-inhibitory concentrations reduces adherence to intestinal cells. The data presented here offer further insight into the antimicrobial activity of carvacrol and show that it has the potential to be used as a natural food antimicrobial against clinically relevant STECs even at sub-inhibitory concentrations. Highlights: Carvacrol has potent antimicrobial activity against O157 and non-O157 STECs. Carvacrol increases cell permeability in O157 and non-O157 STECs. Carvacrol reduces ATP levels in O157 and non-O157 STECs. Carvacrol reduced adherence of STECs to human intestinal epithelial cells.